Novel missense mutation related To KBG syndrome - GEÇKİNLİ, BİLGEN BİLGE; SÖYLEMEZ, MEHMET ALİ (My University, 2020)
Introduction: KBG syndrome (KBGS) (OMIM:#148050) is a rare autosomal dominant disease characterized by short stature, intellectual disability, characteristic facies, skeletal anomalies and macrodontia which mostly effect permanent upper central incisors. Mutations of ANKRD11 gene on 16q24.3 causes KBGS. This gene encodes Ankyrin Repeat Domain-Containing Protein 11 that regulates transcriptional activation. Case: Eight-year-old male patient was referred to our clinic because of having seizures and dysmorphism. He was the fourth child of healthy parents who had a first cousin marriage. His prenatal, natal and postnatal history were unremarkable. He had no developmental delay. At the age of 4, he had his first seizure. His height, weight and OFC(occipitofrontal circumference) were 125 cm (-1.31 SD), 28 kg (-0,19 SD) and 50 cm (-2,11 SD) respectively. He had micro-brachycephaly, thick eyebrows, long eyelashes, long and smooth philtrum, thin upper lip, prominent ears, macrodontia (10 mm), bilateral clinodactyly of fifth fingers. Other systemic examinations were normal. His karyotype was 46,XY and array-CGH was normal. ANKRD11 gene sequencing revealed a heterozygous novel c.4425G>T (p.Arg1475Ser) missense mutation. Segregation analysis showed that it was de novo. Conclusion: Herein we report a novel missense mutation in ANKRD11 gene. Our case will contribute to this syndrome’s genotype-phenotype correlations.
Keywords: KBG; ANKRD11